Natural History of Patients Undergoing Therapeutic Endoscopies for Acute Gastrointestinal Bleeding. Issue 11 (November 2019) - Khoury, Leen; Tobin-Schnittger, Patrick; Champion, Nicholas; Sim, Vasiliy; Gave, Asaf; Hawkins, Samuel; Panzo, Melissa; Cohn, Stephen
When endoscopy is performed for acute GI bleeding, therapeutic endoscopic procedures are infrequently required (only 6% of cases). We sought to determine the natural history of GI hemorrhage in patients who have undergone therapeutic endoscopy. We queried our hospital database for inpatients with acute GI bleeding who underwent therapeutic endoscopy between 2015 and 2017. The primary endpoints were recurrence of bleeding and the subsequent need for repeated endoscopic interventions, angioembolization, or surgery. Demographic information was collected. We reviewed 205 hospitalized patients: mean age was 70 years, 58 per cent were male, and mean hemoglobin was 9 g/dL. Patients had medical conditions predisposing them to bleeding in 59 per cent and history of previous GI bleeding in 37 per cent of cases. Sixty per cent were on antiplatelet/ anticoagulation medications, and 10 per cent were receiving nonsteroidal anti-inflammatory medications. Blood transfusions were given to 78 per cent of patients, with an average of 2.3 units of packed red blood cells transfused per patient before intervention. Recurrence of hemorrhage after therapeutic endoscopy was seen in 9 per cent of patients. Only 2 per cent underwent a second therapeutic endoscopic procedure, and 5 per cent had surgery or angioembolization (half of these patients then had a further recurrence of bleeding). In total, seven patients died (3%). Recurrence of GI bleeding after therapeutic endoscopies is uncommon (9%). Surgery and angioembolization are not commonly necessary, but when used are only successful in 50 per cent of cases.